Utilizing QuillBot Application to Enhance Students Descriptive Text Writing Ability - Muchtar, Rizqi Maulida; Mujahidah, Mujahidah; Sunubi, Abdul Haris; Arqam, Arqam; Dalle, H. Ambo (IAIN KENDARI, 2025)
This study examined the effectiveness of the QuillBot application in enhancing students’ ability to write descriptive texts. Many students struggle with developing their writing skills, particularly in structuring descriptive texts. To address this challenge, technology integration was applied through QuillBot. The research employed a quasi-experimental design involving two groups: an experimental class and a control class. The population consisted of 22 students, with 11 students from the 2024 class (semester 2) as the experimental group and 11 students from the 2023 class (semester 4) as the control group. Data were collected using pre-tests and post-tests. The results revealed that both groups initially had low writing ability, with no significant difference between them (Sig. 0.165 > 0.05). After treatment, the experimental group demonstrated significant improvement (Sig. 0.000 < 0.05), with 64% of students achieving “Average” and 36% “Good.” In contrast, the control group showed no substantial progress, with most students remaining at “Poor” or “Very Poor” levels. Further statistical analyses, including the Mann-Whitney U test, confirmed the effectiveness of QuillBot in improving writing performance. The findings suggest that QuillBot provides a valuable tool for enhancing descriptive text writing compared to conventional methods.